Improving Learning Quality in Pancasila Education Through the NHT Model in Elementary Schools - Ramanda Febriana (Jurnal Multidisiplin Sahombu, 2025)
The writing of this article aims to reanalyze the improvement of learning quality in Pancasila Education through the NHT Model in elementary schools, based on studies previously conducted by experts. This article employs a qualitative literature review method with literature analysis as its analytical instrument. The initial stage of writing this article was determining a topic aligned with the issue the author intended to examine, in order to facilitate the data collection process. The data in this study were obtained through searching online journals on Google Scholar using several keywords, namely learning quality, Pancasila Education, and Numbered Heads Together (NHT). Based on the analysis conducted by the author on previous studies, it can be concluded that the use of the Numbered Heads Together (NHT) model in improving learning quality, particularly in Pancasila Education, has been proven successful. Previous researchers have also stated that improved learning quality is an important factor in enhancing learning outcomes. Through the use of the NHT learning model, students become more enthusiastic and more confident in expressing their opinions, as well as more active in group work, thereby creating an enjoyable learning environment